Transitions in the early years : debating continuity and progression for young children in early education - Fabian, Hilary; Dunlop, Aline-Wendy, 1946- (Routledge/Falmer, 2002)
By the time young children enter statutory education, they may have already attended a number of different educational settings, from entry to group settings outside home to joining playgroup or nursery school. Each of these experiences is likely to affect children's capacity to adjust and to learn.; This volume is focused on children's experiences of personal and curricular transitions in early childhood. The authors are all academics with international reputations in the field of early childhood education. they draw on their research in Europe, Australasia and the USA to consider issues such as: the optimum environment and appropriate pedagogy for young children's learning; how children, parents and educators cope with the transition from home to the first educational settings; and the ways in which professionals can better support and empower children in transition.; The perspectives of children, parents and early years educators are all considered and case study examples are used throughout. This book should be of interest to those involved in working with young children and their families, including students on early years courses, early years practitioners and early years policy makers.